Regulasi Belajar Regulasi Belajar Ditinjau dari Daya Juang dan Sikap Optimis Mahasiswa - Sakdiah, Halimatus; Adawiyah, Rabiatul; Khotimah, Siti Khorriyatul (Jurnal Studia Insania, 2024)
Abstract Self-regulated learning, optimism and adversity quotient is a very important ability for students to be successful in their studies. This study aims to determine the effect of adversity quotient and optimism towards the self-regulated learning. The research method used is a quantitative method with multiple linear regression analysis. The research subjects were all UIN Antasari students, and using simple random sampling techniques, 383 students were selected as samples for this research. The results showed that there was a significant effect adversity quotient on students’ self-regulated learning (r = 0.030). There is an influence of optimism on self-regulated learning of student significantly (r = 0.000). The results of the study also found a significant relationship between adversity quotient and optimism of students (r = 0.000). Then, the results of the study also found that there were influences of adversity quotient and optimism simultaneously (together) towards students' self-regulated learning significantly (r = 0.000). Thus, adversity quotient and optimism are supporting students in self-regulated learning. The better the adversity quotient, optimism of students, the better the self-regulated learning of students. Keywords: Self-regulated Learning. Adversity Quotient, Optimism